Improved Health-Related Quality of Life with Superficial Femoral Artery Stenting in Intermittent Claudication Done Prior to Medical Treatment: A Case Report (Nepalese Journal of Radiology, 2023)
In cases involving TASC A lesions of the superficial femoral artery (SFA), the conventional approach typically starts with medical therapy and supervised exercise. When these measures fail to yield the desired results, endovascular procedures may be contemplated. However, in the distinctive case of a 68-year-old male, endovascular therapy was employed to reestablish blood flow through the obstructed SFA segment. This intervention substantially improved the patient’s ability to walk. Subsequently, the patient continued with optimal medical therapy. This integrated approach, beginning with SFA stenting followed by conservative care, promptly alleviated claudication-related symptoms, ultimately resulting in an enhanced quality of life